MODERASI BERAGAMA DALAM ISLAM DAN RELEVANSINYA DENGAN KONTEKS KEINDONESIAAN - Ahmad Mustafidin (Jurnal Progress)
Abstract The failure to have a dialogue between religious understanding and social reality in Indonesia, which is multicultural, plural, and diverse, is the root of social conflicts with religious backgrounds. The failure to dialogue understanding is experienced by hardline groups who do not want to tolerate and find it difficult to compromise with the understanding of other religions that are different. The main commitment of religious moderation to tolerance makes it the best way to deal with religious radicalism that threatens religious life itself and, in turn, affects the life of community, nation and state unity. Keyword: Moderation of Religion, Indonesian Abstrak Kegagalan dalam mendialogkan pemahaman agama dengan realitas sosial di Indonesia yang multikultural, plural, dan beragam merupakan akar dari konflikkonflik sosial berlatarbelakang agama. Kegagalan mendialogkan pemahaman dialami oleh kelompok garis keras yang tidak mau mentolelir dan sulit berkompromi dengan pemahaman agama lain yang berbeda. Komitmen utama moderasi beragama terhadap toleransi menjadikannya sebagai cara terbaik untuk menghadapi radikalisme agama yang mengancam kehidupan beragama itu sendiri dan, pada gilirannya, mengimbasi kehidupan persatuan bermasyarakat, berbangsa, dan bernegara. Kata Kunci: Moderasi Beragama, Indonesia